Influence of the inflammatory response on treatment of hepatitis C with triple therapy - Winckler, Fernanda Cristina [UNESP]; Marques Braz, Aline Marcia [UNESP]; Silva, Vanessa Nogueira da [UNESP]; Golim, Marjorie de Assis [UNESP]; Andrade, Vanessa Gutierrez de [UNESP]; Abreu Machado, Paulo Eduardo de [UNESP]; Arruda Silveira, Liciana Vaz de [UNESP]; Silva, Giovanni Faria [UNESP] (Soc Brasileira Medicina Tropical, 2018)
Introduction: Chronic hepatitis C is a leading cause of liver disease. Infection triggers an immediate immune response in the host that is mediated by humoral/cellular mechanisms. T cells respond to infection via secretion of cytokines, which inhibit or stimulate one another, leading to cytokine imbalance and ultimately affecting treatment. Studies using interferon (IFN) and ribavirin (RBV) showed that TCD8+ cells and cytokine levels are associated with sustainable virological response (SVR). However, studies that investigated the effects of triple therapy (TT) are limited. Methods: The study included hepatitis C virus (HCV)+ RNA, naives, genotype 1, >= 18 years. and advanced fibrosis (F >= 3) patients. Samples were collected at baseline and after 12 weeks (W12) of TT. Six cytokines were analyzed by flow cytometly. Results: Of 31 patients, four were excluded (two deaths, one interrupted TT, and one F2 patient). Of the 27 remaining patients, 21(78%) were cirrhotic. SVR was achieved in 63% of the patients. The patients had a mean age of 55.11 +/- 10.03 years. Analyses at baseline showed that the chemokine CCL5/Regulated on Activation, Normal T Cell Expressed and Secreted (RANTES) (p=1.04) and interleukin (IL)-6 (p=0.02), which was associated with SVR. RANTES (p=0.04) and IL-8 (p=0.01) levels were associated with SVR at W12. Conclusions: Similar to patterns observed during double therapy, IL-6, IL-8, and RANTES levels were associated with SVR in TT, indicating the potential role of interferon in immune response to hepatitis C virus.
Keywords: Hepatitis C; Cytokine; Treatment